Quantitative high-speed imaging of burned gas temperature and equivalence ratio in internal combustion engines using alkali metal fluorescence. (April 2014) - Mosburger, Michael; Sick, Volker; Drake, Michael C
Alkali metal atoms show an intense natural fluorescence in the burned gas region of internal combustion engines. This fluorescence offers great opportunity for spectroscopic combustion analysis in internal combustion engines without the requirement of laser excitation or image intensifiers. To quantify this fluorescence intensity, spectroscopic and thermodynamic properties of the alkali metals lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs) and their oxidation products and ions were analyzed. Collisional energy transfer and reabsorption effects (including temperature- and pressure-dependent lineshapes) were calculated over the range of engine environments. Three compounds containing Li, Na and K, respectively, were selected as fuel additives for engine experiments. The experiments were conducted on an optical, single-cylinder, spark-ignited, direct-injection research engine, and the fluorescence of the three alkali components was recorded simultaneously using three complimentary metal-oxide semiconductor high-speed cameras. The two-component fluorescence intensity ratios (Na/K, Li/K and Na/Li) are shown to depend on temperature, pressure and equivalence ratio. However, the three-component ratio Na·Li/K 2 is nearly independent of pressure and equivalence ratio in the tested range of operating conditions and can serve as a direct marker for burned gas temperature. Subsequently, equivalence ratio can be determined from any of the bicomponent fluorescence ratios.